Методичні підходи до формування системи ризик-менеджменту - Скопенко, Наталія Степанівна; Захарченко, Іван Сергійович (My University, 2023)
Сучасні умови функціонування у зовнішньому середовищі є досить динамічними та характеризуються високою невизначеністю. У відповідь на це підприємства повинні вчасно виявляти та мінімізувати наслідків настання ризиків, що є основною метою системи ризик-менеджменту. Компанії розплачуються за недооцінку ризиків фінансовими втратами, зниженням вартості акцій і капіталу, зіпсованою репутацією, переведенням цінних співробітників в інші компанії, звільненням топ-менеджерів і навіть банкрутством. У статті розглянуто сутність системи ризик-менеджменту. Представлено та деталізовано етапи ризик-менеджменту. Обґрунтовано потребу у формуванні системи управління ризиками на підприємстві, встановлено основні елементи даної системи та визначено сфери на які спрямовано її вплив. Доведено, що доцільність системного підходу та системного використання методів управління ризиками визначається проблемами сучасного етапу розвитку підприємств, складними ситуаціями, з якими вони стикаються. Розроблено практичні рекомендації щодо створення на підприємстві комплексної системи управління ризиками та визначено методи її ефективного використання. Modern operating conditions in the external environment are quite dynamic and characterized by high uncertainty. In response to this, enterprises must timely identify and minimize the consequences of the occurrence of risks, which is the main goal of the risk management system. Companies pay for underestimating risks with financial losses, a decrease in the value of shares and capital, a damaged reputation, the transfer of valuable employees to other companies, the dismissal of top managers and even bankruptcy. In most cases, risks arise as a result of unsuccessful internal management, unexpected decisions and actions of the company's counterparties in the external environment. Risk management tools and systems are not yet sufficiently developed. At enterprises, each risk is mostly considered separately. In contrast to this approach, risk management in modern theory and practice is considered as a complex management system in the enterprise management system. The feasibility of a systematic approach and systematic use of risk management methods is determined by the problems of the modern stage of development of enterprises, the complex situations they face. The issue of risk management ceases to be considered at the level of a narrow-profile area of the manager's professional activity and becomes the object of direct attention of subjects of managerial activity, regardless of the level of their organizational hierarchy. The process of risk management is constantly becoming more complicated and is becoming an integral element of the management system of enterprises. If the risk is inevitable, then the problem of its assessment, analysis and management becomes especially relevant. The article discusses the essence of the risk management system. The stages of risk management are presented and detailed. The need for the formation of a risk management system at the enterprise is substantiated, the main elements of this system are established, and the areas on which its influence is directed are determined. Practical recommendations on the creation of a complex risk management system at the enterprise and methods of its effective use have been developed.
Keywords: управління ризиками; мінімізація господарських ризиків; ризик-менеджмент; risk management; кафедра економіки праці та менеджменту